2014
DOI: 10.1089/end.2013.0550
|View full text |Cite
|
Sign up to set email alerts
|

What About Conventional Laparoscopic Radical Cystectomy? Cost-Analysis of Open Versus Laparoscopic Radical Cystectomy

Abstract: Within our series, LRC is a cost neutral minimally invasive alternative to ORC without comprising quality of care and with beneficial perioperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…A recent study reported that LRC had lower costs compared to ORC (17.534 Euros compared to 22.284 Euros, respectively; p not significant). Authors emphasize that costs with disposable surgical equipment in LRC are compensated by lower transfusion rates, shorter hospital length and less intensive care admissions ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that LRC had lower costs compared to ORC (17.534 Euros compared to 22.284 Euros, respectively; p not significant). Authors emphasize that costs with disposable surgical equipment in LRC are compensated by lower transfusion rates, shorter hospital length and less intensive care admissions ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…We initially identified 315 studies from PubMed, Web of Science, and Cochrane Library databases. Of the 315 studies, 11 were included in this study [11, 13, 1927]. The characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic surgery is suggested to have crucial advantages in terms of reduced postoperative pain, shorter hospital stay, less analgesic requirement, and faster recovery time. Laparoscopic surgery including RPS has been continued to be used and developed over the past decade to improve cosmetic results and to reduce patient invasiveness (Hermans et al, 2014;Tang et al, 2014;Aboumarzouk et al, 2013).…”
Section: Outcomes and Complications Of Simultaneous Laparoscopic Cystmentioning
confidence: 99%